Solid-liquid equilibrium solubility measurement, model evaluation and Hansen solubility parameter of thiamethoxam in three binary solvents. (July 2021) - Sha, Jiao; Cao, Zidan; Hu, Xiaoran; Huang, Zibo; Chang, Yingge; Wan, Yameng; Sun, Renren; Jiang, Gaoliang; He, Haixia; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of thiamethoxam in three binary solvent mixtures was measured. The miscibility of thiamethoxam in mixed solvents was demonstrated by HSP. Solubility data was correlated by five models. The mixing thermodynamic properties of thiamethoxam dissolution were evaluated. Abstract: This work determined the mole fraction solubility of thiamethoxam in three binary solvent mixtures ((DMSO, DMA and acetic acid) + methanol) under the conditions of "T = 278.15 K to 323.15 K" and " p  = 0.1 MPa". The results demonstrated that with the increase of temperature and co-solvent mass fraction, the measured solubility of thiamethoxam increases in all the solvent mixtures studied. The results of using Hansen solubility parameters to investigate the affinity between thiamethoxam and the three mixed solvents studied indicate that this affinity may be caused by a combination of factors. Five thermodynamic models including modified Apelblat model, λh model, Wilson model, NRTL model and UNIQUAC model were used to regress the experimental solubility data of thiamethoxam in the three binary solvent mixtures. It was found that the UNIQUAC model and the modified Apelblat model correlated the experimental solubility more accurately than the other three models. In addition, the mixed thermodynamic properties for mixing process of thiamethoxam in different mixed solvents were estimated and discussed in term of Wilson model and experimental solubility data of thiamethoxam. Moreover, Wilson model was used to calculate the mixing thermodynamic parameters (Δmix G, Δmix H, Δmix S ) of the mixing process of thiamethoxam. All Δmix G and Δmix H values are negative and Δmix S values are positive, which indicate that the mixture process of thiamethoxam in all the binary solvent mixtures studied is an entropy driven and spontaneous endothermic process.